Environmental knowledge, pro-environmental behaviour and energy savings in households: An empirical study. (15th December 2016) - Pothitou, Mary; Hanna, Richard F.; Chalvatzis, Konstantinos J.
Highlights: Environmental values and energy saving in households are positively correlated. Environmental knowledge and household energy saving are positively correlated. Household energy saving is linked to gender and employment status. Abstract: In this paper we evaluate the impact of knowledge about environmental and energy issues on potential pro-environmental behaviour in households, specifically relating to behaviours, attitudes and habits towards energy use. Our results are based on an empirical survey and we find significant correlations which indicate that residents with positive environmental values and greater environmental knowledge are more likely to demonstrate energy behaviours, attitudes and habits which lead to energy saving activities in households. This is further supported through a Principal Component Analysis (PCA), which suggests that energy saving behaviour may also vary according to gender and employment status. Conversely, we find only limited evidence of statistical associations between environmental predisposition and knowledge, and ownership and frequency of use of household appliances. We argue that our results contribute to the significant body of literature supporting the role of knowledge in active engagement with energy issues. This study is timely following closely policy developments in active consumer engagement by the European Commission.